Transformasi Bisnis UMKM Sanfresh Melalui Digitalisasi Bisnis Pasca Covid 19 - Budi Harto; Teti Sumarni; Andina Dwijayanti; Rita Komalasari; Santi Widyawati (Universitas Persada Indonesia YAI, 2023)
Sanfresh is a small and medium business in the Cicalengka district that is still lagging behind in thelatest business technology, all of their marketing activities and financial recording processes for businessesstill rely on manual processes. The purpose of this community service is to help Sanfresh MSMEs becomean MSMEs that have better marketing tools and activities that can help sales, another goal is also Sanfreshhas digital-based financial records that can make it easier to analyze sales. The method used in this communityservice is survey, interview, giving material and practicum. The results of dedication to Sanfresh includecreating a more representative company logo, product catalogues and attractive product photos, registeringSanfresh on the Shopee platform, GoMart, to making a website to make marketing activities easier, anddigital-based financial reports.